Nano-drug delivery system for pancreatic cancer: A visualization and bibliometric analysis - Zhao, Jie-Feng; Zou, Fei-Long; Zhu, Jin-Feng; Huang, Chao; Bu, Fan-Qin; Zhu, Zheng-Ming; Yuan, Rong-Fa (Frontiers in Pharmacology, 2022)
Background Nano drug delivery system (NDDS) can significantly improve the delivery and efficacy of drugs against pancreatic cancer (PC) in many ways. The purpose of this study is to explore the related research fields of NDDS for PC from the perspective of bibliometrics. Methods Articles and reviews on NDDS for PC published between 2002 and 2021 were obtained from the Web of Science Core Collection. CiteSpace, VOSviewer, R-bibliometrix, and Microsoft Excel are comprehensively used for bibliometric and visual analysis. Results A total of 1384 papers on NDDS for PC were included. The number of papers showed an upward trend over the past 20 years. The USA had the most papers, followed by China, and India. Also, the USA had the highest number of total citations and H-index. The institution with the most papers was Chinese Acad Sci, which was the most important in international institutional cooperation. Wang J of Zhejiang Univ, Couvreur P from Univ Paris Saclay, and Kataoka K from Univ Tokyo have made the most important contributions to this field. JOURNAL OF CONTROLLED RELEASE published the most papers and has been cited the most. “Cancer-associated fibroblast”, “exosome”, “hypoxia”, and other topics related to the TME, “stimuli-responsive” and “autophagy”, and PC treatment-related topics such as “immunotherapy” and “combination therapy” are the research hotspots and trends in the field of NDDS for PC. Conclusion This study systematically uncovered a holistic picture of the performance of NDDS for PC-related literature over the past 20 years. We provided scholars to understand key information in this field with the perspective of bibliometrics, which we believe may greatly facilitate future research in this field.